KAJIAN EKONOMIS BAJA TULANGAN BETON - Biatna Dulbert T; Denny Wahyudi (Badan Standardisasi Nasional, 2008)
Steel is one of the strategic products. Its using can influence national economy and national development. Impactof steel using is concern with safety aspect to its users. National Standardization Agency of Indonesia (BSN) haveestablished SNI 07-2052-2002 and then it was adopted as technical regulation, so this SNI became mandatory.Now that of this SNI has been mandatory, producer and infrastructure should have been ready to apply this SNI.Economic benefit of applying this SNI in national can be taken if either sub-standard local or import products arenot circulate in the market anymore, so the total economic benefit in applying this standard is Rp.4.141.905.428.338. This standard Application which is not comprehensive can be burden for producer who applySNI and circulation of the illegal product will more and more luster and can’t be dammed up. So we need toimprove quality related to conformity assessment body, surveillance and standard harmonization.